Speech coding for Bluetooth with CVSD algorithm - Khalifa, Othman Omran; Khan, Sheroz; Islam, Md. Rafiqul; Muktar, Mohd; Yaacob, Zahrein (2004)
Speech coding is a procedure used to represent a digital speech signal by as minimum bits as possible, maintaining at the same time a reasonable level of speech quality. Due to increasing demand for speech communications, speech coding technology has received a lot o f researcher's interests. Speech coding is performed using numerous steps or operations specified as an algorithm. This paper presents the Continuously Variable Slope Delta (CVSD) speech coding method which is widely used in Bluetooth applications. It is a nonlinear sampled data feedback system which accepts a band limited analog signal and encodes it into binary form for transmission through a digital channel. At the receiver, the binary signal is decoded into a close approximation of original analog signal. This coding technique is implemented in Matlab Simulink and the simulation results shown coding has good noise immunity. Further, shown in this work is the fact that damaged packets are discarded straight away without having a serious impact on the speech quality making it more suitable for two way audio communications.